Electronic Structures of Nickel(II)-Bis(indanyloxazoline)-dihalide Catalysts: Understanding Ligand Field Contributions That Promote C(sp2)-C(sp3) Cross-Coupling - McNicholas, Brendon J; Tong, Z Jaron; Bím, Daniel; Turro, Raymond F; Kazmierczak, Nathanael P; Chalupský, Jakub; Reisman, Sarah E; Hadt, Ryan G (Inorganic chemistry, 2023)
NiII(IB) dihalide [IB = (3aR,3a'R,8aS,8a'S)-2,2'-(cyclopropane-1,1-diyl)bis(3a,8a-dihydro-8H-indeno[1,2-d]-oxazole)] complexes are representative of a growing class of first-row transition-metal catalysts for the enantioselective reductive cross-coupling of C(sp2) and C(sp3) electrophiles. Recent mechanistic studies highlight the complexity of these ground-state cross-couplings but also illuminate new reactivity pathways stemming from one-electron redox and their significant sensitivities to reaction conditions. For the first time, a diverse array of spectroscopic methods coupled to electrochemistry have been applied to NiII-based precatalysts to evaluate specific ligand field effects governing key Ni-based redox potentials. We also experimentally demonstrate DMA solvent coordination to catalytically relevant Ni complexes. Coordination is shown to favorably influence key redox-based reaction steps and prevent other deleterious Ni-based equilibria. Combined with electronic structure calculations, we further provide a direct correlation between reaction intermediate frontier molecular orbital energies and cross-coupling yields. Considerations developed herein demonstrate the use of synergic spectroscopic and electrochemical methods to provide concepts for catalyst ligand design and rationalization of reaction condition optimization.